Variability in soil physical-chemical properties along the root-explored profile in deep Oxisols of commercial eucalypt plantations - Silva, Vinicius Evangelista; Rodrigues Nogueira, Thiago Assis [UNESP]; Abreu-Junior, Cassio Hamilton; Jani, Arun Dilipkumar; Buzetti, Salatier [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; He, Zhenli; Ganga, Antonio; Andrade Penido, Tamires Mousslech; Silva, Anderson Rodrigo da; Capra, Gian Franco (Elsevier B.V., 2021)
While deep soils commonly characterize tropical forests, direct measurements of soil physical & ndash;chemical properties, fine root distributions, and relationships among them are scarce. In this paper, we report results from a project in Brazil that were obtained from experimental areas selected for their representative tropical climatic and edaphic features. Our objective was to evaluate vertical and spatial soil physical & ndash;chemical properties along the root-explored profile of Eucalyptus plantations to better understand the relationship between each component. Soil was collected from four sites (Tre circle s Lagoas-Site 13, Mogi Gua & ccedil;u-20, Telemaco Borba-22, and Bocaiuva30) and characterized for physical & ndash;chemical properties (pH, texture, organic matter, cation exchange capacity, and nutrient content) and fine root density (FRD). Soil was sampled up to 2 m beyond the deepest observed roots, or until a cemented horizon or R layer was detected. Spatial variability was investigated through a geostatistical approach using ordinary kriging. Data were subjected to ANOVA as well as bi- and multivariate statistics using a correlation matrix and robust principal factor analysis (PFA), respectively. Results showed that investigated Oxisols reached the maximum depth of 19 (Site 13), 8 (20), 11 (22), and 8 (30) m. In most investigated sites (20, 22, and 30) and for most soil properties, a typical soil horizonation was observed along the first 2.5/3.0 m. Deeper horizons (>3.0 m) of clayey Oxisols were characterized by the presence of typical porthole shapes dramatically interrupting soil horizonation, indicating spatial pedovariability and demonstrating underestimates of vertical and spatial pedovariability can occur under standard soil investigations to 2.0 m in depth. Correlation matrix and PFA showed that Eucalyptus roots strongly affected most investigated soil properties. Our study considered vertical and spatial dimensions of soil physical & ndash;chemical properties as well as the deep-rooting properties of Eucalyptus, which is critical for improving soil management in infertile Eucalyptus plantations.
Keywords: Pedovariability; Root system; Tropical soils; Geostatistics; TECHS project